A high-wear-resistant antibacterial ceramic tile based on ceramic waste and a preparation method thereof
Patent Information
- Application Number
- CN202611319822.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-23
AI Technical Summary
目前这些废料大多被填埋或丢弃,不仅浪费资源,还对环境造成一定的污染
(1)本发明通过在坯体中引入碳化硅和氧化铝作为增强剂,在釉层中引入纳米氧化锆耐磨剂分级匹配,坯体和釉层的耐磨增强剂相互配合,在提高产品强度和耐磨性能的同时,改善了坯釉间的热膨胀系数匹配度,从而减少釉面裂纹的产生。同时,坯体增强抑制了釉层裂纹扩展,釉层耐磨则保护了坯体不受磨损,坯体和釉层相互作用,促进了产品强度和耐磨性能的提升。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building ceramics technology, specifically relating to a high wear-resistant and antibacterial ceramic brick based on ceramic waste and its preparation method. Background Technology
[0002] The production of ceramic products generates a large amount of waste, including waste from the ceramic body, glaze, and broken ceramic products. Statistics show that the waste rate in ceramic production reaches 8-15%. Currently, most of this waste is landfilled or discarded, which not only wastes resources but also pollutes the environment. Furthermore, traditional building ceramic tiles are prone to surface wear and bacterial growth during use, especially in high-frequency use areas such as public places, kitchens, and bathrooms, placing higher demands on the wear resistance and antibacterial properties of ceramic tiles.
[0003] Existing technologies for producing ceramic tiles using ceramic waste mostly suffer from problems such as low waste addition ratios, insufficient product strength, and poor wear resistance, and they also struggle to simultaneously achieve antibacterial functions. Ceramic tiles with antibacterial properties generally rely on adding expensive antibacterial agents, resulting in high production costs and difficulty in maintaining the antibacterial effect long-term. Furthermore, traditional ceramic tile manufacturing processes often suffer from high firing temperatures, high energy consumption, and high scrap rates, which are inconsistent with the current trend of green and low-carbon industrial development.
[0004] Therefore, developing a type of ceramic tile that can efficiently utilize ceramic waste, possesses high wear resistance and long-lasting antibacterial properties, and has an environmentally friendly and energy-saving manufacturing process has become a pressing technical challenge for the ceramic industry. It also aligns with the industry's innovative direction of solid waste utilization and functional upgrading, and has significant industrial value and application prospects. Summary of the Invention
[0005] This invention aims to solve at least one of the technical problems existing in the prior art. To this end, this invention proposes a high-wear-resistant and antibacterial ceramic brick based on ceramic waste and its preparation method. By selecting specific raw materials and optimizing their proportions and preparation process, this invention achieves a high proportion of recycling of ceramic waste, while endowing the ceramic brick with excellent wear resistance and long-lasting antibacterial properties. This not only reduces production costs and environmental pollution but also meets market demand for multifunctional and environmentally friendly ceramic products.
[0006] To solve the above-mentioned technical problems, a first aspect of the present invention provides a ceramic tile, comprising a green body and a glaze layer covering the upper surface of the green body, wherein the raw material components of the green body include green body waste, glaze layer waste, base green body, modified antibacterial agent and reinforcing agent; the reinforcing agent includes silicon carbide and alumina, the modified antibacterial agent includes nano zinc oxide and nano silver, and the modifier of the modified antibacterial agent includes a silane coupling agent; The raw material components of the glaze include glaze waste, base glaze, wear-resistant agent and flux. The wear-resistant agent includes nano-zirconia, and the flux includes spodumene and xenotime.
[0007] Specifically, the preparation of ceramic tiles using waste materials from the green body and glaze layer presents challenges. Due to the large fluctuations in the composition and uneven activity of the waste materials, the amount of liquid phase during firing is difficult to control. When the amount added is high, the strength and wear resistance of the product will decrease significantly. At the same time, the green body waste contains a high content of metal oxides such as Fe2O3 and TiO2, which are prone to coordination reactions with antibacterial agents, encapsulating and blocking antibacterial active sites, thereby reducing the antibacterial properties and durability of the product. The glass phase and the wear-resistant phase in the glaze layer waste have a large difference in thermal expansion coefficients, which easily leads to microcracks during the cooling process, resulting in defects such as pinholes and crazing on the glaze surface.
[0008] To address this, the present invention introduces silicon carbide and alumina as reinforcing agents into the body. Specifically, alumina reacts in situ with the high-content silica in the waste to form mullite crystals, while silicon carbide provides a high-hardness framework, filling the pores between waste particles. Nano-zirconia is introduced into the glaze layer for graded matching; the thermal expansion coefficient of zirconia is highly compatible with the glassy phase in the glaze waste. Therefore, the wear-resistant reinforcing agents in the body and glaze layer work synergistically to improve product strength and wear resistance, while also enhancing the compatibility of thermal expansion coefficients between the body and glaze, reducing glaze cracking. Simultaneously, during the firing process, Al2O3 in the body diffuses into the glaze layer, eliminating abrupt changes at the body-glaze interface; ZrO2 in the glaze layer reacts with SiO2 on the body surface to form zircon (ZrSiO4) crystals, improving interfacial bonding strength. Therefore, the body reinforcing agent inhibits glaze crack propagation, and the wear-resistant glaze layer protects the body from wear. Meanwhile, single nano-zinc oxide has a narrow antibacterial spectrum, is ineffective against Staphylococcus aureus, and is prone to forming zinc-aluminum spinel and becoming inactive in the high Al2O3 system of ceramic waste; single nano-silver is prone to discoloration and agglomeration, and Ag in the presence of Fe2O3 in ceramic waste + It is easily reduced to elemental Ag and loses its antibacterial activity. To address this, this invention employs a composite antibacterial agent of hydrophobically modified nano-zinc oxide and nano-silver, wherein: zinc oxide provides a continuous supply of hydroxyl radicals, and Ag... + It disrupts bacterial cell membranes, exhibiting a dual bactericidal effect; furthermore, zinc oxide can react with the high silica content in ceramic waste to form a zinc silicate crystalline phase, fixing Ag. + This prevents its migration and loss, thereby improving the antibacterial properties of the product.
[0009] Furthermore, this invention uses a mixture of spodumene and xenotime as a flux, wherein: the Li in spodumene (Li₂O·Al₂O₃·4SiO₂) contains Li +With a strong fluxing field and high fluxing efficiency, it can form a eutectic with the high Al2O3 content in ceramic waste, thus lowering the firing temperature; the Y³ content in xenotime ore (YPO4) + It can stabilize the tetragonal phase of ZrO2 and work synergistically with the wear-resistant nano ZrO2 to retain the phase transformation toughening effect of ZrO2, which is beneficial to improving the wear resistance of the glaze.
[0010] In some embodiments of the present invention, the chemical composition of the waste billet, by weight percentage, includes: SiO2 62-68%, Al2O3 22-28%, Fe2O3 0.5-1.2%, TiO2 0.3-0.8%, CaO 0.3-0.8%, MgO 0.2-0.6%, K2O 1.5-2.5%, Na2O 1-2%, and loss on ignition 3-5%.
[0011] In some embodiments of the present invention, the chemical composition of the glaze waste, by weight percentage, includes: SiO2 55-62%, Al2O3 12-18%, Fe2O3 0.3-0.8%, CaO 8-12%, MgO 3-6%, K2O 1-2%, Na2O 1-2%, and loss on ignition 2-5%.
[0012] In some embodiments of the present invention, the average particle size of the green body waste and glaze waste is 3-5 μm.
[0013] In some embodiments of the present invention, the preparation process of the modified antibacterial agent includes the following steps: dispersing nano zinc oxide and nano silver in anhydrous ethanol at a mass ratio of (5-8):1, adding silane coupling agent, stirring and refluxing at 80-100°C for 1-2 hours, condensing and refluxing, centrifuging, washing, and drying to obtain the modified antibacterial agent.
[0014] In some embodiments of the present invention, the amount of the silane coupling agent is 2-3 wt% of the total amount of nano zinc oxide and nano silver.
[0015] Specifically, this invention uses a silane coupling agent to modify the surface of the antibacterial agent to be hydrophobic. The silane coupling agent forms a steric hindrance layer, which can not only prevent Fe from entering the ceramic waste. 3+ Direct contact with antibacterial sites to prevent Fe 3+ It is toxic; moreover, it can make the antibacterial agent evenly dispersed in the green body, avoid agglomeration, and improve the long-lasting antibacterial effect.
[0016] In some embodiments of the present invention, the mass ratio of silicon carbide to aluminum oxide is (2-3):1; for example, it can be any mass ratio among 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1 or any range of mass ratios between the two.
[0017] In some embodiments of the present invention, the mass ratio of spodumene to xenotime is (2-3):1; for example, it can be any mass ratio among 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, 3:1 or any range of mass ratios between the two.
[0018] In some embodiments of the present invention, the basic blank material comprises, by weight: 15-25 parts kaolin, 10-18 parts quartz sand, and 5-12 parts feldspar.
[0019] In some embodiments of the present invention, the chemical composition of the base glaze, by weight percentage, includes: 45-52% SiO2, 18-25% Al2O3, 3-6% CaO, and 2-4% MgO.
[0020] In some embodiments of the present invention, the raw material components of the green body include, by weight: 30-40 parts of green body waste, 15-20 parts of glaze waste, 30-55 parts of basic green body, 1-3 parts of modified antibacterial agent, and 0.5-2 parts of reinforcing agent.
[0021] In some embodiments of the present invention, the raw material components of the glaze layer include, by weight: 20-30 parts of glaze waste, 45-55 parts of base glaze, 3-8 parts of wear-resistant agent, and 5-10 parts of flux.
[0022] A second aspect of the present invention provides a method for preparing the above-mentioned ceramic brick, comprising the following steps: The waste material of the green body and the waste material of the glaze layer are calcined separately to obtain calcined waste material of the green body and calcined waste material of the glaze layer. The calcined green body waste and calcined glaze waste are mixed with other raw material components of the green body and then wet ball milled to obtain a green body slurry. The calcined glaze waste is mixed with other glaze raw material components and then wet ball milled to obtain a glaze slurry. The slurry is spray-dried to obtain a powder; the powder is then pressed to form a body; the glaze is applied to the upper surface of the body to form a glaze layer; after drying, it is fired to obtain the ceramic tile.
[0023] In some embodiments of the present invention, the calcination temperature is 800-900℃. Calcination of ceramic waste can remove impurities and organic matter, improve the activity of the waste, and thus increase the proportion of waste added.
[0024] In some embodiments of the present invention, the firing temperature regime is as follows: first, the temperature is raised from room temperature to 600-700°C at a rate of 8-12°C / min and held for 20-30 min; then, the temperature is raised to 1220-1260°C at a rate of 4-7°C / min and held for 5-10 min; then, the temperature is lowered to 950-1000°C at a rate of 1-3°C / min and held for 15-25 min; finally, the temperature is allowed to cool naturally to room temperature.
[0025] Specifically, this invention employs a gradient segmented firing temperature regime to further improve the overall performance of the product. Wherein: The first stage (room temperature rises to 600-700℃): The temperature is increased at a moderate rate of 8-12℃ / min and held for 20-30 minutes. This stage primarily aims to smoothly remove residual moisture from the body and allow organic matter such as silane coupling agents and residual impurities in ceramic waste to slowly oxidize and volatilize. If the temperature rises too quickly, the rapid escape of moisture and gases will cause defects such as pinholes and bubbles in the body or glaze. This holding stage ensures the complete removal of organic matter, providing a pure physical structure for subsequent high-temperature firing and preventing damage to the body-glaze interface due to gas release during the high-temperature stage.
[0026] The second stage (heating to the highest temperature from 600-700℃): This stage is the core period for liquid phase generation, densification, and the development of key crystalline phases. A slower heating rate of 4-7℃ / min allows the flux to fully exert its effect, forming a eutectic with the high alumina in the waste and promoting sintering. It also provides sufficient time for the alumina in the green body and the silica in the waste to fully react in situ, forming mullite crystals. Simultaneously, it promotes the reaction of ZrO2 and SiO2 at the green body-glaze interface to form zircon (ZrSiO4) crystalline phase, enhancing the interfacial bonding strength. A short holding time at the highest temperature (5-10 min) ensures complete densification of the green body and full melting and flattening of the glaze layer, while avoiding excessive liquid phase, green body deformation, and high-temperature loss or agglomeration and deactivation of antibacterial active ingredients such as nano-silver caused by prolonged high-temperature holding.
[0027] The third stage (maximum temperature reduced to 950-1000℃): Cooling at a slow rate of 1-3℃ / min with intermediate temperature holding is the critical period for stress release and precipitation of specific crystalline phases. Slow cooling facilitates the full precipitation of the zinc silicate crystalline phase, thereby effectively encapsulating and fixing Ag. + This prevents its migration and loss, enhancing its long-lasting antibacterial effect; simultaneously, this slow cooling process, combined with the Y content in xenotime ore... 3+ The stabilizing effect helps retain the tetragonal phase of ZrO2, allowing it to exert its phase transformation toughening effect and improve the wear resistance of the glaze. In addition, slow cooling and medium-temperature heat preservation can effectively release the residual thermal stress caused by the difference in thermal expansion coefficients between the body and the glaze layer, preventing defects such as glaze cracking and peeling caused by excessively rapid cooling.
[0028] The fourth stage (natural cooling to room temperature): After stress relief and crystal precipitation in the intermediate temperature stage, the product can be directly cooled to room temperature to achieve final shaping. This ensures the stability of the product structure and does not require additional energy consumption, meeting the requirements of energy-saving and consumption-reducing production.
[0029] In some embodiments of the present invention, the firing atmosphere is an oxidizing atmosphere, which is conducive to the full sintering of the body and the glaze layer and improves the mechanical properties of the product.
[0030] Compared with the prior art, the above-described technical solution of the present invention has at least the following technical effects or advantages: (1) This invention introduces silicon carbide and alumina as reinforcing agents into the body and introduces nano-zirconia wear-resistant agents into the glaze layer in a graded and matched manner. The wear-resistant reinforcing agents of the body and the glaze layer work together to improve the product's strength and wear resistance, while also improving the matching degree of thermal expansion coefficients between the body and the glaze, thereby reducing the generation of glaze cracks. At the same time, the body reinforcement inhibits the propagation of glaze cracks, while the wear resistance of the glaze layer protects the body from wear. The interaction between the body and the glaze layer promotes the improvement of the product's strength and wear resistance.
[0031] (2) This invention employs a modified antibacterial agent of nano-zinc oxide and nano-silver, wherein: zinc oxide provides sustained hydroxyl radicals, and Ag... + It disrupts bacterial cell membranes; simultaneously, zinc oxide reacts with the high silica content in ceramic waste to form a zinc silicate crystalline phase, fixing Ag. + To prevent its migration and loss, dual sterilization enhances the product's antibacterial properties.
[0032] (3) The present invention uses a mixture of spodumene powder and xenotime as a flux, wherein: Li in spodumene + With a strong fluxing field and high fluxing efficiency, it can form a eutectic with high Al2O3 in ceramic waste, thus lowering the firing temperature; Y³ in xenotime ore + It can stabilize the tetragonal phase of ZrO2 and work synergistically with the wear-resistant nano ZrO2 to retain the phase transformation toughening effect of ZrO2, thus jointly improving the wear resistance of the glaze.
[0033] (4) In the preparation of ceramic bricks of the present invention, the activity of ceramic waste is improved by calcining pretreatment, thereby increasing the proportion of waste added; and a specific firing preparation is adopted to promote the precipitation of crystals in the glaze and the phase transformation toughening effect of ZrO2, thereby achieving the product performance improvement under a high proportion of ceramic waste incorporation. Detailed Implementation
[0034] The present invention will now be described in detail with reference to embodiments to facilitate understanding of the invention by those skilled in the art. It is particularly important to note that the embodiments are merely illustrative of the invention and should not be construed as limiting the scope of protection of the invention. Non-essential improvements and adjustments made to the invention by those skilled in the art based on the above description should still fall within the scope of protection of the invention. Furthermore, all raw materials mentioned below, unless otherwise specified, are commercially available products; all process steps or preparation methods not mentioned in detail are process steps or preparation methods known to those skilled in the art.
[0035] Example 1 A ceramic tile includes a body and a glaze layer covering the upper surface of the body. Wherein: The raw material components of the green body, by weight, include: 35 parts of green body waste, 18 parts of glaze waste, 20 parts of kaolin, 15 parts of quartz sand, 8 parts of feldspar, 2 parts of modified antibacterial agent, 1.2 parts of silicon carbide, and 0.6 parts of alumina.
[0036] The preparation process of the modified antibacterial agent includes the following steps: nano zinc oxide (particle size 40nm) and nano silver (particle size 15nm) in a mass ratio of 6:1 are dispersed in anhydrous ethanol, silane coupling agent KH-550 (the amount added is 2.5% of the total mass of nano zinc oxide and nano silver) is added, and the mixture is stirred and refluxed at 90°C for 1.5 hours. After reflux and centrifugation at 8000 rpm, the mixture is washed three times with anhydrous ethanol and dried under vacuum at 105°C to obtain the modified antibacterial agent.
[0037] The raw material components of the glaze layer, by weight, include: 25 parts of glaze waste, 50 parts of basic glaze, 5 parts of nano-zirconia (particle size 30nm), 4 parts of spodumene, and 2 parts of xenotime ore.
[0038] The chemical composition of the blank waste, by weight percentage, includes: SiO2 65%, Al2O3 25%, Fe2O3 0.8%, TiO2 0.5%, CaO 0.5%, MgO 0.4%, K2O 2.0%, Na2O 1.5%, and loss on ignition 4.3%.
[0039] The chemical composition of the glaze waste, by weight percentage, includes: SiO2 60%, Al2O3 15%, Fe2O3 0.5%, CaO 12%, MgO 6%, K2O 1.5%, Na2O 1.5%, and loss on ignition 3.5%.
[0040] The chemical composition of the base glaze, by weight percentage, includes: 48% SiO2, 21% Al2O3, 4.5% CaO, 3.0% MgO, and the balance being 23.5%.
[0041] A method for preparing ceramic tiles includes the following steps: (1) The waste material of the green body and the waste material of the glaze layer are crushed and ground to D50=3.2μm, and then calcined at 850℃ for 2.5 hours to obtain calcined waste material of the green body and calcined waste material of the glaze layer. (2) The calcined green body waste and calcined glaze waste are mixed with the raw material components of other green bodies and wet ball milled to D50=3.2μm to obtain green body slurry; (3) The calcined glaze waste is mixed with the raw material components of other glazes and wet ball milled to D50=2.5μm to obtain glaze slurry; (4) Spray dry the body slurry to obtain body powder; then press the body powder into shape to obtain a body with a thickness of 10mm; then apply glaze slurry to the upper surface of the body to form a glaze layer of 1.0mm; after drying, fire in an oxidizing atmosphere to obtain ceramic bricks.
[0042] The firing temperature regime is as follows: first, the temperature is increased from room temperature to 650℃ at a rate of 10℃ / min and held for 30min; then, the temperature is increased to 1220℃ at a rate of 5℃ / min and held for 8min; then, the temperature is decreased to 980℃ at a rate of 3℃ / min and held for 20min; finally, the temperature is allowed to cool naturally to room temperature.
[0043] Example 2 A ceramic tile includes a body and a glaze layer covering the upper surface of the body. Wherein: The raw material components of the green body, by weight, include: 38 parts of green body waste, 16 parts of glaze waste, 18 parts of kaolin, 12 parts of quartz sand, 10 parts of feldspar, 2.5 parts of modified antibacterial agent, 1.4 parts of silicon carbide, and 0.6 parts of alumina.
[0044] The preparation process of the modified antibacterial agent includes the following steps: nano zinc oxide (particle size 30nm) and nano silver (particle size 20nm) in a mass ratio of 5:1 are dispersed in anhydrous ethanol, silane coupling agent KH-550 (2% of the total mass of nano zinc oxide and nano silver) is added, the mixture is stirred and refluxed at 80°C for 2 hours, after reflux and centrifugation at 8000rpm, the mixture is washed 3 times with anhydrous ethanol, and then vacuum dried at 105°C to obtain the modified antibacterial agent.
[0045] The raw material components of the glaze layer, by weight, include: 30 parts of glaze waste, 50 parts of basic glaze, 4 parts of nano-zirconia (particle size 20nm), 5 parts of spodumene, and 2 parts of xenotime ore.
[0046] The chemical composition of the blank waste, by weight percentage, includes: SiO2 66%, Al2O3 24%, Fe2O3 0.8%, TiO2 0.6%, CaO 0.5%, MgO 0.4%, K2O 2.0%, Na2O 1.5%, and loss on ignition 4.2%.
[0047] The chemical composition of the glaze waste, by weight percentage, includes: SiO2 62%, Al2O3 18%, Fe2O3 0.8%, CaO 8%, MgO 3.2%, K2O 2%, Na2O 2%, and loss on ignition 4%.
[0048] The chemical composition of the base glaze, by weight percentage, includes: 45% SiO2, 25% Al2O3, 3% CaO, 4% MgO, and the balance being 23%.
[0049] The ceramic brick preparation method of Example 1 was used, except that the maximum firing temperature was changed to 1240°C.
[0050] Example 3 A ceramic tile includes a body and a glaze layer covering the upper surface of the body. Wherein: The raw material components of the green body, by weight, include: 40 parts of green body waste, 20 parts of glaze waste, 15 parts of kaolin, 12 parts of quartz sand, 6 parts of feldspar, 1.5 parts of modified antibacterial agent, 1.5 parts of silicon carbide, and 0.5 parts of alumina.
[0051] The preparation process of the modified antibacterial agent includes the following steps: nano zinc oxide (particle size 50nm) and nano silver (particle size 10nm) in a mass ratio of 8:1 are dispersed in anhydrous ethanol, silane coupling agent KH-550 (3% of the total mass of nano zinc oxide and nano silver) is added, the mixture is stirred and refluxed at 100℃ for 1 hour, after reflux and centrifugation at 8000rpm, the mixture is washed 3 times with anhydrous ethanol, and then vacuum dried at 105℃ to obtain the modified antibacterial agent.
[0052] The raw material components of the glaze layer, by weight, include: 20 parts of glaze waste, 55 parts of basic glaze, 8 parts of nano-zirconia (particle size 50nm), 6 parts of spodumene, and 2 parts of xenotime ore.
[0053] The chemical composition of the blank waste, by weight percentage, includes: SiO2 67%, Al2O3 22%, Fe2O3 1.2%, TiO2 0.8%, CaO 0.8%, MgO 0.6%, K2O 2.5%, Na2O 2%, and loss on ignition 3.1%.
[0054] The chemical composition of the glaze waste, by weight percentage, includes: SiO2 62%, Al2O3 14%, Fe2O3 0.5%, CaO 12%, MgO 4.5%, K2O 1.5%, Na2O 1.5%, and loss on ignition 4%.
[0055] The chemical composition of the base glaze, by weight percentage, includes: 52% SiO2, 18% Al2O3, 6% CaO, 4% MgO, and the balance being 20%.
[0056] The ceramic brick preparation method of Example 1 was used, except that the maximum firing temperature was changed to 1260°C.
[0057] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the waste material of the green body and the waste material of the glaze layer were not calcined in the preparation method of the ceramic tile.
[0058] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that nano titanium dioxide (particle size 30-50nm) was used instead of nano zinc oxide in the modified antibacterial agent.
[0059] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that equal amounts of nano-zirconia are used to replace silicon carbide and aluminum oxide.
[0060] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that an equal amount of silicon carbide is used instead of nano-zirconia.
[0061] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that equal amounts of potassium feldspar and sodium feldspar are used to replace spodumene and xenotime, respectively. Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the firing temperature regime is different. The temperature is increased from room temperature to 1220°C at a rate of 10°C / min and held for 8 minutes; then it is naturally cooled to room temperature.
[0062] Performance testing The ceramic tile samples prepared in Examples 1-3 and Comparative Examples 1-6 were tested for flexural strength, abrasion resistance, hardness, and antibacterial properties. Specifically, the flexural strength of the tile body and the abrasion resistance of the glaze were tested according to standards GB / T3810.4-2016 and GB / T3810.7-2016, and the antibacterial properties and durability of the glaze against Escherichia coli and Staphylococcus aureus were tested according to JC / T897-2014. The results are shown in Table 1.
[0063] Table 1:
[0064] As shown in Table 1, the ceramic tile samples prepared in Examples 1-3 of the present invention all have high flexural strength, hardness and wear resistance, and the antibacterial rate and durability against Escherichia coli and Staphylococcus aureus are maintained at a high level. The glaze surface is smooth and flat with no obvious defects.
[0065] Compared with Example 1, Comparative Example 1 did not perform calcination pretreatment on the ceramic waste, so the organic matter and other impurities in the waste were not removed, and the waste had low activity, resulting in insufficient liquid phase during firing and a decrease in the density of the green body. At the same time, the volatilization of impurities caused pinholes and microcracks to appear on the glaze, significantly reducing the flexural strength and wear resistance. Furthermore, the reaction of impurities with the antibacterial agent led to a decrease in the antibacterial rate.
[0066] Comparative Example 2, compared to Example 1, used nano-titanium oxide instead of zinc oxide. The absence of zinc oxide prevented it from reacting with the high silica content in the ceramic waste to form a zinc silicate crystal phase, resulting in Ag... + Migration and loss are likely to occur during firing and use; at the same time, the lack of continuous hydroxyl radical synergistic bactericidal effect provided by zinc oxide leads to a significant decrease in the product's antibacterial durability (especially against Staphylococcus aureus).
[0067] Compared to Example 1, Comparative Example 3 uses nano-zirconia instead of silicon carbide and alumina. Although nano-zirconia has a certain reinforcing effect, it cannot form mullite crystals in situ with silicon dioxide in the waste, and lacks the high-hardness skeleton support of silicon carbide, resulting in a significant decrease in the flexural strength and wear resistance of the ceramic tile. In addition, the mismatch of the thermal expansion coefficients between the body and the glaze leads to slight cracking on the glaze surface.
[0068] Compared with Example 1, Comparative Example 4 uses silicon carbide instead of nano-zirconia. Since silicon carbide cannot achieve a good match with the glass phase in the glaze waste in terms of thermal expansion coefficient, nor can it react with SiO2 on the surface of the body to generate zircon crystal phase to enhance the interfacial bonding, the glaze gloss deteriorates, the wear resistance decreases, and the flexural strength of the body is also reduced due to the weakening of the interfacial bonding.
[0069] Compared to Example 1, Comparative Example 5 uses potassium feldspar and sodium feldspar instead of spodumene and xenotime. Feldspar fluxes are inefficient and cannot form eutectic compounds with high Al2O3, resulting in insufficient liquid phase at firing temperature, non-dense sintering of the green body, and decreased strength and wear resistance. Simultaneously, it lacks the Y³⁺ found in xenotime. + The stabilizing effect of the tetragonal ZrO2 phase is lost, resulting in the loss of the phase transformation toughening effect and a deterioration in the glaze quality.
[0070] Compared to Example 1, Comparative Example 6 employed a direct heating and natural cooling firing process. Because the low-temperature holding and impurity removal stage was omitted, organic matter and moisture were removed too quickly, resulting in pinholes and microcracks remaining in the body and glaze. Simultaneously, the lack of a slow cooling and medium-temperature holding stage prevented the zinc silicate crystalline phase from fully precipitating to fix Ag.+ This leads to a significant decrease in the antibacterial durability rate; moreover, the thermal stress is not released, and the toughening effect of ZrO2 phase transformation is damaged, resulting in a significant deterioration in the mechanical properties and glaze quality of the product.
[0071] In summary, all the raw material components and preparation processes of this invention (waste calcination, antibacterial agent modification, combination of reinforcing agent and wear-resistant agent, specific fluxing agent and firing temperature regime) are indispensable. Only through the synergistic effect of the technical solution of this invention can ceramic tiles with high strength, high wear resistance, long-lasting antibacterial effect and excellent glaze quality be prepared.
[0072] For those skilled in the art, several simple deductions or substitutions can be made without departing from the inventive concept, without requiring creative effort. Therefore, any simple improvements made to this invention by those skilled in the art based on the disclosure of this invention should be within the scope of protection of this invention. The above embodiments are preferred embodiments of this invention, and all processes similar to this invention and equivalent changes should fall within the scope of protection of this invention.
Claims
1. A ceramic tile, characterized in that, The material includes a green body and a glaze layer covering the upper surface of the green body. The raw material components of the green body include green body waste, glaze layer waste, basic green body material, modified antibacterial agent, and reinforcing agent. The reinforcing agent includes silicon carbide and alumina. The modified antibacterial agent includes nano zinc oxide and nano silver. The modifier of the modified antibacterial agent includes a silane coupling agent. The raw material components of the glaze include glaze waste, base glaze, wear-resistant agent and flux. The wear-resistant agent includes nano-zirconia, and the flux includes spodumene and xenotime.
2. The ceramic tile according to claim 1, characterized in that, The chemical composition of the waste billet, by weight percentage, includes: SiO2 62-68%, Al2O3 22-28%, Fe2O3 0.5-1.2%, TiO2 0.3-0.8%, CaO 0.3-0.8%, MgO 0.2-0.6%, K2O 1.5-2.5%, Na2O 1-2%, and loss on ignition 3-5%. And / or, the chemical composition of the glaze waste, by weight percentage, includes: SiO2 55-62%, Al2O3 12-18%, Fe2O3 0.3-0.8%, CaO 8-12%, MgO 3-6%, K2O 1-2%, Na2O 1-2%, and loss on ignition 2-5%.
3. The ceramic tile according to claim 1, characterized in that, The preparation process of the modified antibacterial agent includes the following steps: dispersing nano zinc oxide and nano silver in anhydrous ethanol at a mass ratio of (5-8):1, adding silane coupling agent, stirring and refluxing at 80-100℃ for 1-2 hours, condensing and refluxing, centrifuging, washing, and drying to obtain the modified antibacterial agent.
4. The ceramic tile according to claim 1, characterized in that, The mass ratio of silicon carbide to alumina is (2-3):1; and / or the mass ratio of spodumene to xenotime is (2-3):
1.
5. The ceramic tile according to claim 1, characterized in that, The basic blank material includes, by weight, 15-25 parts of kaolin, 10-18 parts of quartz sand, and 5-12 parts of feldspar. And / or, the chemical composition of the base glaze, by weight percentage, includes: 45-52% SiO2, 18-25% Al2O3, 3-6% CaO, and 2-4% MgO.
6. The ceramic tile according to claim 1, characterized in that, The raw material components of the green body, by weight, include: 30-40 parts of green body waste, 15-20 parts of glaze waste, 30-55 parts of basic green body, 1-3 parts of modified antibacterial agent, and 0.5-2 parts of reinforcing agent.
7. The ceramic tile according to claim 1, characterized in that, The raw material components of the glaze layer include, by weight: 20-30 parts of glaze waste, 45-55 parts of base glaze, 3-8 parts of wear-resistant agent, and 5-10 parts of flux.
8. A method for preparing ceramic tiles as described in any one of claims 1-7, characterized in that, Includes the following steps: The waste material of the green body and the waste material of the glaze layer are calcined separately to obtain calcined waste material of the green body and calcined waste material of the glaze layer. The calcined green body waste and calcined glaze waste are mixed with other raw material components of the green body and then wet ball milled to obtain a green body slurry. The calcined glaze waste is mixed with other glaze raw material components and then wet ball milled to obtain a glaze slurry. The slurry is spray-dried to obtain a powder; the powder is then pressed to form a body; the glaze is applied to the upper surface of the body to form a glaze layer; after drying, it is fired to obtain the ceramic tile.
9. The method for preparing ceramic bricks according to claim 8, characterized in that, The calcination temperature is 800-900℃.
10. The method for preparing ceramic bricks according to claim 8, characterized in that, The firing temperature regime is as follows: first, the temperature is raised from room temperature to 600-700℃ at a rate of 8-12℃ / min and held for 20-30min; then, the temperature is raised to 1220-1260℃ at a rate of 4-7℃ / min and held for 5-10min; then, the temperature is lowered to 950-1000℃ at a rate of 1-3℃ / min and held for 15-25min; finally, the temperature is allowed to cool naturally to room temperature.